ChemInform Abstract: Synthesis of Novel 7‐Substituted Pyrido[2′, 3′:4, 5]furo[3, 2‐d]pyrimidin‐4‐amines (VII) and Their N‐Aryl Analogues (IX) and Evaluation of Their Inhibitory Activity Against Ser/Thr Kinases. Issue 19 (13th May 2014) - Deau, Emmanuel; Loidreau, Yvonnick; Marchand, Pascal; Nourrisson, Marie‐Renee; Loaec, Nadege; Meijer, Laurent; Levacher, Vincent; Besson, Thierry
Abstract Among the compounds synthesized derivative (VIIb) shows the best inhibitory activity and appears to be specific to CLK1 among the panel of the tested kinases.